Cyberintimacy Involvement on Building Emotional Intimacy in Close Relationship on Indonesian Tinder Users - Fahira Syifa Machfudz; Rino Febrianno Boer; Nicky Wongso (Ikatan Sarjana Komunikasi Indonesia, 2021)
Tinder, as one of the most popular online dating applications, is nicknamed as the hookup app. The negative perceptions inherent among the public were born because of how users in western countries operate the application, which does not follow the norms adopted in Indonesia. Many people assume that most Tinder users are those who are not looking for a long-term romantic relationship. The possibility of getting a partner who will commit to the relationship is not a common idea. This research aims to understand the development process of emotional intimacy and the initiation of a close relationship between Tinder users who have managed to find their partner through the Tinder application and communication mediated by computers (internet). This research uses a qualitative approach. In-depth interviews and Netnographic observations were used as the primary and secondary data collection techniques. This study indicates that although many Tinder users in Indonesia use Tinder similar to how people in western countries do, many users have finally succeeded in building long-term close relationships. Therefore, the perception about small numbers of Tinder users looking for long-term romantic relationships is not accurate.